Madzhabu Ar-Rumantikiyyah Fiil Adab Al-Arabi Al-Hadist ma’a al-Istimror wa At-Taghyir - Agus Yasin; Annisa Fithri Lathiifah; Zamzam Dwi Saputra (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2023)
PurposeThis study aims to explain the flow of romanticism along with the continuity and changes to con-temporary Arabic literature, and to be able to reveal dialogues about the flow of romanticism in modern Arabic literature, which is growing rapidly in the Arab world. Knowing the characteris-tics of Arabic literary Romanticism. Knowing the figures of Arabic Literary Romanticism. MethodThis study used a library research design and note-taking techniques. This research method uses aspects of library research with data sourcesof books and literacy related to romanticism in mod-ern Arabic literature: continuity and change. Results/FindingsThis study reveals the continuity and change as well as its influence on contemporary Arabic lit-erature, namely: 1) History of Arabic Literature in the modern era, 2) History of the Emergence of Western Romanticism in Arabic and its characteristics, 3) Development of Romanticism and its influence on Arabic Literature, 4) Figures of the Romanticism of Arabic Literature and their works. ConclusionRomanticism has had a major influence on Arabic literature, with the establishment of groups of Arabic literary, such as the Mahjar group, the Diwan school, the Apollo school and Usbah al-Asyrah. In addition, there is also a renewal of magazines and newspapers in the Arab world which call for renewal, and criticism of the previous flow (classicism).